Fauna and biotopic distribution of Chrysomelidae (Coleoptera) in the Zhiguli State Nature Reserve, Russia - Sergei V. Dedyukhin (Nature Conservation Research: Заповедная наука, 2023)
Chrysomelidae (hereinafter – leaf beetles) forms one of the largest families of trophically specialised phytophagous beetles. Therefore, a detailed study of leaf beetles is an important component of research aiming to assess the diversity and specificity of biota in Protected Areas. Based on the results of original studies (2011, 2013, 2014, 2021) and a critical review of the literature, this paper presents the species composition and analyses the fauna of leaf beetles in the Zhiguli State Nature Reserve, Russia. It was found that the studied fauna belongs to the richest local faunas of leaf beetles in the Middle Volga Region, and it has a considerable originality. In total, 230 leaf beetle species have been recorded in the study area. Of them, 47 species were recorded for the first time in the Zhiguli State Nature Reserve, including 23 species recorded for the first time for the fauna of the Samara Region. The leaf beetle fauna is characterised by a complex composition, including species of European, Siberian and Kazakh-Turanian faunas, and it includes a relict endemic of Eastern Europe, Chrysolina roddi. An analysis of the biotopic distribution of leaf beetles showed that the highest number of species (116) is represented in the forb and petrophytic steppes of the Zhiguli Mountains. It also includes quite rich complexes of semi-aquatic and meadow biotopes of the floodplain and islands of the River Volga (98 species), as well as upland forest (93 species) (including broad-leaved forests and pine forests). In the Zhiguli State Nature Reserve, trophically specialised leaf beetle species are associated with plants from 38 families. Their most numerous groups are related with Asteraceae (28 species), Salicaceae (23 species), Brassicaceae (17 species), and Lamiaceae (15 species). The leaf beetle fauna of the Zhiguli State Nature Reserve can be considered one of a reference group in the forest-steppe of the Volga Upland. This confirms its great importance for the preservation of the original natural ecosystems in the Middle Volga Region.